2012
DOI: 10.1097/brs.0b013e31826cb8f5
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Adjacent-Level Ossification Development After Surgery in the Cervical Spine

Abstract: We recommend that the surgeon make every effort to keep the plate as far away from the adjacent disc as possible. Strength of Statement: Strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“…Age, sex, levels of surgery, indications for surgery, and the carpentry of arthroplasty were the reported factors that could affect the formation of HO after cervical arthroplasty. 6,18,24,35,36,42,44 In the literature, short to midterm clinical outcomes of cervical arthroplasty were not significantly impaired by HO. 34,[40][41][42] There was also heterogeneity in both location and morphology of HO formation.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, levels of surgery, indications for surgery, and the carpentry of arthroplasty were the reported factors that could affect the formation of HO after cervical arthroplasty. 6,18,24,35,36,42,44 In the literature, short to midterm clinical outcomes of cervical arthroplasty were not significantly impaired by HO. 34,[40][41][42] There was also heterogeneity in both location and morphology of HO formation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that CDA is safe and effective with equivalent or superior clinical outcome to anterior cervical decompression and fusion, 11,22 but whether CDA can reduce ASD remains controversial. Kim et al 17 performed a systematic review and found that CDA showed lower rates of adjacent-level ossification development compared with ACDF at both short-and long-term follow-up. Garrido et al 10 reported that CAD with Bryan cervical disc prosthesis (Medtronic Sofamor Danek) was associated with a lower incidence of adjacent-level ossification compared with arthrodesis with plate fixation at 2-and 4-year follow-up evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…For PS, the entry point was previously described to be on the anterior edge of the C2 end plate and a few millimeters lateral to the midline, on the side ipsilateral to the C1-C2 joint to be fixated [1][2][3]. We moved the entry point 5 mm cranially to decrease the risk of adjacent level ossification [23,24] at C2-C3. In addition, we moved the entry point to the side contralateral to the C1-C2 joint to be fixated, to maintain a transcorporal pathway for the screw and to minimize the possibility of the screw cutting out of the anterior cortex of the C2 promontory.…”
Section: Screw Entry Pointsmentioning
confidence: 99%
“…1, Top), to provide an allowable distance between the screw head and the C2-C3 intervertebral disc to prevent adjacent level ossification development [23,24]. For facet screws (CF, MF, and LF), the area below the anterior prominent ridge of the axis was divided into medial and lateral parts by a vertical line bisecting the anterior margin of the C1-C2 facet joint.…”
Section: Screw Entry Points and Trajectoriesmentioning
confidence: 99%